Food for Special Medical Purposes: A Global Review of Usage Trends, Regulatory Frameworks, and Key Growth Drivers - Hae Jin Kang; Yoo Kyoung Park (Clinical nutrition research, 2025)
This review offers a comprehensive analysis of food for special medical purposes (FSMPs)― specially formulated foods designed to support the dietary management of individuals with specific medical conditions. The regulatory frameworks governing FSMP differ significantly across key regions, including the European Union, North America (with a focus on the United States), and Asia (primarily China and India). FSMP is critical in addressing malnutrition, metabolic disorders (including inborn errors of metabolism), and chronic diseases, such as cancer, diabetes, and neurological conditions. Recent advancements, such as the application of three-dimensional printing technology and the growing emphasis on personalized nutrition, are poised to revolutionize the FSMP industry. The global market for FSMP is experiencing rapid growth, particularly in China, driven by factors like aging populations and the increasing prevalence of chronic diseases. Future trends suggest a shift toward more personalized, technologically advanced FSMP formulations. However, challenges such as high costs, limited accessibility, unclear regulations, and poor palatability must be addressed to maximize the potential of FSMP in enhancing patient care.